Emergency general surgery specific frailty index: A validation study. Issue 2 (August 2016) - Orouji Jokar, Tahereh; Ibraheem, Kareem; Rhee, Peter; Kulavatunyou, Narong; Haider, Ansab; Phelan, Herb A.; Fain, Mindy; Mohler, Martha Jane; Joseph, Bellal
Abstract : INTRODUCTION: Assessment of operative risk in geriatric patients undergoing emergency general surgery (EGS) is challenging. Frailty is an established measure for risk assessment in surgical cases. The aim of our study was to validate a modified 15-variable EGS-specific frailty index (EGSFI). METHODS: We prospectively collected geriatric (age older than 65 years) EGS patients for 2 years. Postoperative complications were collected. Frailty index was calculated for 200 patients based on their preadmission condition using 50-variable modified Rockwood frailty index. Emergency general surgery–specific frailty index was developed based on the regression model for complications and the most significant factors in the frailty index. Receiver operating characteristic curve analysis was performed to determine cutoff for frail status. We validated our results using 60 patients for predicting complications. RESULTS: A total of 260 patients (developing, 200; validation, 60) were enrolled in this study. Mean age was 71 ± 11 years, and 33% developed complications. Most common complications were pneumonia (12%), urinary tract infection (9%), and wound infection (7%). Univariate analysis identified 15 variables significantly associated with complications that were used to develop the EGSFI. A cutoff frailty score of 0.325 was identified using receiver operating characteristic curve analysis for frail status. Sixty patients (frail, 18; nonfrail, 42) were enrolled in the validation cohort. Frail patients were more likely to have postoperative complications (47% vs. 20%; p < 0.001) compared to nonfrail patients. Frail status based on EGSFI was a significant predictor of postoperative complications (odds ratio, 7.3; 95% confidence interval, 1.7–19.8; p = 0.006). Age was not associated with postoperative complications (odds ratio, 0.99; 95% confidence interval, 0.92–1.06; p = 0.86). CONCLUSION: The 15-variable validated EGSFI is a simple and reliable bedside tool to determine the frailty status of patients undergoing EGS. Frail status as determined by the EGSFI is an independent predictor of postoperative complications and mortality in geriatric EGS patients. LEVEL OF EVIDENCE: Prognostic study, level II.